3D models related to the publication: New insights into the diversity of strepsirrhine primates from the late early – early middle Eocene of North Africa (Algeria and Tunisia) - (:unkn) unknown (My University, 2025)
This contribution contains the three-dimensional digital models of the dental fossil material of strepsirrhine primates (Azibiidae and ?Djebelemuridae) from the late early to early middle Eocene of the Gour Lazib Complex in western Algeria and of Djebel Chambi in central-western Tunisia. These fossils were described, figured and discussed in the following publication: Marivaux et al. (2025), New insights into the diversity of strepsirrhine primates from the late early – early middle Eocene of North Africa (Algeria and Tunisia). Journal of Human Evolution, 103729.
Keywords: African Research